2015
DOI: 10.1136/thoraxjnl-2014-206287
|View full text |Cite
|
Sign up to set email alerts
|

Role of primary care in the follow-up of patients with obstructive sleep apnoea undergoing CPAP treatment: a randomised controlled trial

Abstract: Clinical Trials NCT01918449.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
0
48
0
2
Order By: Relevance
“…In the present study, we performed an additional analysis considering the same cost for sleep studies in the PC and SU settings, which showed that the management of a patient via PC generated a savings of €117.16. Second, 8 of the 11 participating PC centres had participated in a previous study by our group12 and had previously received specific training in managing patients with OSA before completing the new education programme. Therefore, there was no complete uniformity in the experience in the PC group with respect to education programmes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we performed an additional analysis considering the same cost for sleep studies in the PC and SU settings, which showed that the management of a patient via PC generated a savings of €117.16. Second, 8 of the 11 participating PC centres had participated in a previous study by our group12 and had previously received specific training in managing patients with OSA before completing the new education programme. Therefore, there was no complete uniformity in the experience in the PC group with respect to education programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of the 11 participating PC centres that participated in a previous study by our group12 had previously received specific training in managing patients with OSA before completing the new education programme. This programme included the theoretical and practical aspects of managing patients with sleep apnoea and comprised specific information about the diagnosis of sleep apnoea and treatment decisions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-inferiority margin of −1 hour of PAP adherence was determined by consensus of the investigators and has been used in previous studies comparing different models of care for SDB. 28 The study will require 138 patients (69 in each arm) to achieve 90% power with a type I error of 0.05, using this non-inferiority margin and a SD of 2 hours of nightly CPAP use. 48 The SD used in the sample size calculation was based on the results of two previous studies.…”
Section: Sample Sizementioning
confidence: 99%
“…Elimination of the requirement for board certification and center accreditation for reimbursement for routine OSA management. Although controversial (15), evidence (16)(17)(18) suggests that nonspecialist care is as effective and less expensive than specialist care for OSA.…”
Section: What Is the Future Of Sleep Medicine In The United States?mentioning
confidence: 99%